Detection of Exoenzyme Effectors and Determination The MIC of Antibiotics for Pseudomonas Aeruginosa Isolated from Ear Infections Patients in Basrah Province, Iraq - Ayad Abdulhadi Waham 1 / Lina A. Naser2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Ear infections are a common health problem, the most common microorganism which cause of infection is Pseudomonas aeruginosa. The study aimed to detection for bacterium ability of virulence factors production, molecular detection on that Exoenzyme effectors. The results of P. aeruginosa is the most type at18.62%.  This bacterium was had a high level of resistance to the Ticarcillin antibiotic at 73.69%, were 10% of isolates (MDR), 42% (XDR) and 5% (PDR), production was each of the biofilm at 89.47%, protease enzyme at 79.94%, and Metallo beta-lactamase at 47.36%. Presence of exoenzyme genes (exoS:57.89%, exoT: 84.21%, exoU: 73.68% and exoY: 89.47%).